A comparison of speech intelligibility and subjective quality with hearing-aid processing in older adults with hearing loss. - Arehart, Kathryn H.; Chon, Song Hui; Lundberg, Emily M. H.; Harvey Jr., Lewis O.; Kates, James M.; Anderson, Melinda C.; Rallapalli, Varsha H.; Souza, Pamela E. (International Journal of Audiology, 2022)
This study characterised the relationship between speech intelligibility and quality in listeners with hearing loss for a range of hearing-aid processing settings and acoustic conditions. Binaural speech intelligibility scores and quality ratings were measured for sentences presented in babble noise and processed through a hearing-aid simulation. The intelligibility–quality relationship was investigated by (1) assessing the effects of experimental conditions on each task; (2) directly comparing intelligibility scores and quality ratings for each participant across the range of conditions; and (3) comparing the association between signal envelope fidelity (represented by a cepstral correlation metric) and intelligibility and quality. Participants were 15 adults (7 females; age range 59–81 years) with mild to moderately severe sensorineural hearing loss. Intelligibility and quality showed a positive association both with each other and with changes to signal fidelity introduced by the entire acoustic and signal-processing system including the additive noise and the hearing-aid output. As signal fidelity decreased, quality ratings changed at a slower rate than intelligibility scores. Individual psychometric functions were more variable for quality compared to intelligibility. Variability in the intelligibility–quality relationship reinforces the importance of measuring both intelligibility and quality in clinical hearing-aid fittings.